Letter from the editor - Díez-Martín, Francisco (Journal of Management and Business Education, 2020)
This letter introduces number 2, volume 3 (2020), of the Journal of Management and Business Education. This number is made up of five works related to: the origin and evolution of the management of legitimacy in higher education; the use of kpi to measure student satisfaction as an indicator of university management: optimizing the selection and training of professionals using artificial intelligence; educational branding in Spanish private universities and; the use of robots in education. In addition, thanks to all those who have made possible the publication of this number.